Synthesis and Absolute Configuration of (20R)-20-Acetyl-23,24- bisnorcholanic Lactones Prepared from (E)-(20S,25R)- and (E)-(20S,25S)- 20,23-Diacetylfurost-22-enes - Víctor Gómez Calvario (Journal of the Mexican Chemical Society, 2007)
The synthesis of (20R)-20-acetyl-23,24-bisnorcholaniclactones from (E)-(20S,25R)- and (E)-(20S,25R)-20,23-diacetylfurost-22-enes (derived from diosgenin, hecogenin and sarsasapogenin)is reported. The configuration of the stereogenic center at C-20 wasdetermined by NMR and single crystal X-ray diffraction studies. Thelactones can be used in the synthesis of a variety of steroidal derivatives.